Penerapan Model PBL dengan Pendekatan Saintifik dalam Pembelajaran Rasio untuk Meningkatkan Hasil Belajar - Noor Laily Anggraini; Sunarno Sunarno (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
This study aims to improve the learning outcomes of sixth-grade students on the topic of ratio equivalence through the implementation of the Problem-Based Learning (PBL) model with a scientific approach. The research employed a Classroom Action Research (CAR) design conducted in two cycles. Data were collected through student activity observations and learning outcome tests, covering the cognitive, affective, and psychomotor domains. The results showed a significant improvement in all three aspects. Student activity reached the "very active" category, and student achievement in all domains exceeded the minimum classical mastery criteria. These findings indicate that the PBL model based on a scientific approach is effective in mathematics instruction to comprehensively enhance student learning outcomes.